Effect of post-training meals on blood glucose and blood pressure in young soccer athletes: Intervention and correlational study - Dewi, Luthfia; Nugraheni, Kartika; Mustakim, Mustakim; Rosidi, Ali; Yogaswara, Andre; Muhibbi, Muhammad (Jurnal Keolahragaan, 2025)
Macronutrient content of post-exercise meal is a fundamental for achieving optimal recovery following exercise training. This study aimed to analyze the effects of a high-fat meal consumed after training on blood glucose and pressure levels in young male soccer athletes. Furthermore, examining the relationship among body composition variables was a secondary objective. A pre-post intervention study was conducted with 34 male soccer athletes (age: 16 ± 0.8 years). Participants consumed a high-fat meal (-45% of total intake 1061 kcal) immediately after strenuous training. Blood samples were collected at baseline, immediately post-training, and 1 h post-training to assess trends in blood glucose and pressure levels. Bioelectrical impedance analysis (BIA) was used to measure participant characteristics. Statistical analysis was performed using one-way repeated measures ANOVA followed by post hoc Bonferroni tests to determine significant differences between groups. Pearson correlation analysis was conducted to examine the relationships among the body composition variables. The average skeletal muscle mass and body fat percentage were approximately 59% and 24.6%, respectively. Glucose levels remained unchanged immediately after training but increased significantly by ~17% (p < 0.001) 1 h later. Systolic blood pressure (SBP) decreased by ~5% (p = 0.03) at 1 h post-training, while diastolic blood pressure (DBP) exhibited minimal change (p = 0.06). A correlation analysis indicated an inverse relationship between body mass and skeletal muscle mass, contrasting with the linear relationship between body mass and body fat. The results suggest that a high-fat meal consumed after exercise may lead to an increase in glucose levels 1 h post-exercise. The slight reduction in SBP observed 1 h post-training may represent a normal physiological response to exercise. Since the current study did not have the exercise-only group, further research is needed to confirm whether the change of the blood glucose levels was mainly from the diet.